2013
DOI: 10.1093/jrr/rrs141
|View full text |Cite
|
Sign up to set email alerts
|

Study of antioxidative effects and anti-inflammatory effects in mice due to low-dose X-irradiation or radon inhalation

Abstract: Low-dose irradiation induces various stimulating effects, especially activation of the biological defense system including antioxidative and immune functions. Oxidative stress induced by reactive oxygen species (ROS) can cause cell damage and death and can induce many types of diseases. This paper reviews new insights into inhibition of ROS-related diseases with low-dose irradiation or radon inhalation. X-irradiation (0.5 Gy) before or after carbon tetrachloride (CCl4) treatment inhibits hepatopathy in mice. X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 68 publications
(82 reference statements)
3
53
0
2
Order By: Relevance
“…Many of these effects persisted at 9 months. Our results are in accordance with some reports showing the anti-inflammatory effect of low-dose irradiation [51,61] and of low dose radiotherapy (<1Gy or fractionated) [62][63][64].…”
Section: Discussionsupporting
confidence: 93%
“…Many of these effects persisted at 9 months. Our results are in accordance with some reports showing the anti-inflammatory effect of low-dose irradiation [51,61] and of low dose radiotherapy (<1Gy or fractionated) [62][63][64].…”
Section: Discussionsupporting
confidence: 93%
“…37 Unfortunately, in our experimental setting we cannot provide data about wild-type mice irradiated with 0.5 Gy. However, as proposed by Kataoka et al 38 and others low-dose radiation rather activates the anti-oxidative defense systems in the body, than induces oxidative stress and therefore contributes to preventing or reducing ROS-related injuries. In contrast, enhanced oxidative stress and reduced oxidative capacity is one hallmark in A-T patients and the deficiency to counteract ROS-induced DNA damage also contributes to the phenotype in Atm-deficient mice.…”
Section: Discussionmentioning
confidence: 94%
“…Electronic products emitted the light causes damage to the retina by free radical attacks, which is a common phenomenon [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to ultraviolet (UV) A and short-wavelength visible radiation, from environment, may induce the production of reactive oxygen species (ROS) and result in oxidative damage to RPE cells [1,2,3]. Oxidative injury and functional impairment may act an early and important role in the development of age-related macular degeneration (AMD) [2,4,5,6], Previous studies have indicated that damage to RPE through photochemical mechanisms by free radical reactions is driven by photo-excited, endogenous chromophores through the cornea and lens [2].…”
Section: Introductionmentioning
confidence: 99%